External Validation of Difficult-to-Treat Resistance Prevalence and Mortality Risk in Gram-Negative Bloodstream Infection Using Electronic Health Record Data From 140 US Hospitals. (28th February 2019) - Kadri, Sameer S; Lai, Yi Ling (Elaine); Ricotta, Emily E; Strich, Jeffrey R; Babiker, Ahmed; Rhee, Chanu; Klompas, Michael; Dekker, John P; Powers, John H; Danner, Robert L; Adjemian, Jennifer; ,
Abstract: Difficult-to-treat resistance (DTR; ie, co-resistance to all first-line antibiotics) in gram-negative bloodstream infection (GNBSI) is associated with decreased survival in administrative data models. We externally validated DTR prevalence and associated mortality risk in GNBSI using detailed clinical data from electronic health records to adjust for baseline differences in acute illness severity.